Evaluation of Non-Medical Goods Logistics Management at El Syifa Kuningan General Hospital - Ihsan Haris Munandar; Arlette Suzy Puspa Pertiwi; Bambang Sukajie (Research of Service Administration Health and Sains Healthys, 2025)
In an organization that requires a lot of work, like a hospital, non-medical logistical management is essential. Hospital services in different sections run smoothly because to logistics management. Frequent stock shortages in storage warehouses are one example of how many hospitals fall short of logistics management standards, which eventually results in hospital losses and no additional implementation evaluation. According to the study's findings, the El Syifa Kuningan public hospital's logistics management implementation is still lacking. Starting with subpar planning, budgeting, procurement that takes too long due to lengthy procedures, storage, distribution, deletion, and monitoring that needs to be reviewed on a regular basis. In order to enhance hospital services, a logistics management evaluation was conducted based on the current issues in order to improve the logistics management procedure for non-medical commodities. Improvements to the logistics management system for non-medical commodities in line with the logistics management cycle are suggested by the research's findings in order to facilitate better implementation.